Análise de atividades de complementação curricular na área de educação ambiental e suas contribuições à alfabetização científica - Ubinski, Juliana Alves da Silva (2016)
To provide an education that can form critical citizens, active and transformers of society, far from being a contemporary challenge, it permeates debates and inspires educational theories long ago. One of the proposals to contribute to the achievement of this goal is the expansion of the school day. Although the debates on the subject can refer to an idea of recent and innovative proposal, in Brazil, experiences with full-time education focused for less economically favored social classes are realities for at least five decades. During this period, there were beginnings and closures cycles with these experiences. However, although there are several debates between advocates and opponents of this educational policy, there are not so many researches that address the impacts of these activities for teachers and students involved in these proposals. Through research that discusses and reflects on expansion programs of the school day, it is expected to be possible to ascertain whether the practice performed contributes to the goals proposed for the program. In this sense, through this study, it is intended to determine whether the activities in the area of environmental education, linked to programs of expansion of the school day in state schools of Cascavel-PR, contribute to the achievement of the main objective of the journey expansion programs school: reduce educational inequalities (BRAZIL, 2010). Therefore, Scientific Literacy indicators will be used to enable verifying the level of scientific literacy of students in the subjects addressed in the extracurricular activities they are enrolled. Analysis of the legislation was made which regulates the expansion of the school day, in the proposals of activities in the field of environmental education and also interviews with teachers and students involved in the activities. The different stages of the research show that some gaps in the legislation that regulates the extracurricular activities can negatively impact the development and results of the activities. Among the five analyzed activities, it was possible to realize the contribution of only one for Scientific Literacy of the students. It is noticed that there is still a long way to go in order that the extracurricular activities, at least in most cases, contribute to student learning and, consequently, for education.